Analisis Implementasi Good Corporate Governance Dan Penerapan PSAK No.109 Tentang Akuntansi Zakat Pada Lembaga Amil Zakat Yayasan Solopeduli Ummat - Anggit Kartika Candraningsih; Endang Masitoh Wahyungsih; Purnama Siddi (ITB AAS INDONESIA Surakarta, 2020)
In this study aims to test and analyzer the Amil Zakat Institution Solopeduli Foundation has implemented the principles of Good Corporate Governance and test the consistency of the presentation of zakat and infaq / alms accounting at the mop Zakat Institution Solopeduli Foundation in accordance with PSAK No. 109. The results of this study indicate that the Implementation of Good Corporate Governance and SFAS 109 at the Solopeduli Foundation have been effectively implemented. The management of zakat, donation / alms in the Solopeduli Foundation has referred to the principles of Good Corporate Governance and in its financial recording and reporting refers Tto PSAK 109 so as to create effectiveness in the management of zakat, infaq / alms. The distribution of zakat is based on the priority scale of the Solopeduli Foundation prioritizing the Orphans and the Poor. This study aims to determine the effect of Return On Assets, Price. Keywords: GCG, PSAK 109, Solopeduli Ummat Foundation, Amil Zakat.